Russia’s Arctic Strategy in the Greater Eurasian Partnership - I. F. Kefeli; A. V. Nikolaenko (EURASIAN INTEGRATION: economics, law, politics, 2022)
This study focuses on the role of the Arctic Strategy of Russia in the Great Eurasian Partnership.Aim. The study aims to identify the features of the Arctic Strategy of Russia in the Great Eurasian Partnership.Tasks. The development of principles of geopolitical forecasting and work with big data, with the aim of synchronizing the integration processes contradictory in nature and interests of the actors in Greater Eurasia, identifying the features of the geopolitical regionalization of Eurasia, and analyzing the global security analytics of the Great Eurasian Partnership in the coming “digital era”.Methods. The transition from the “analog” to the “digital era” at the beginning of the 21st century meant an essentially revolution in the data itself, which was associated with the emergence of their new quality — predictive. The methodology for research and forecasting the prospects of Eurasian integration is modeling the multi-agent interaction of geopolitical factors of coalitions based on mathematical game theory. The strategy of transition to a polycentric world order implies the need to move from “geopolitical fiction” to geopolitics, based on mathematical modeling of global geopolitics processes using game theory methods.Results. The geopolitical regionalization of Eurasia is a challenge to time. On the expanses of the Eurasian continent, several multi-format long-term “Eurasian projects” are increasingly clearly emerging. This is, firstly, the Eurasian Economic Union, secondly, the Chinese One Belt-One Way and, thirdly, Indo-Pacifica. The Russian Arctic is a region of the Great Eurasian Partnership. The tasks of the modern Arctic policy of Russia are focused on ensuring the priority growth of raw materials exports and industrial development of the Arctic territories, rather than on solving the problems of improving the quality of life of the local population, although in the Russian Arctic strategy until 2035 these tasks are formulated quite correctly.Conclusion. The analytics of the Eurasian partnership and ...